Case Report: Peripheral Ulcerative Keratitis in Systemic Solid Tumour Malignancies - Foo, Valencia Hui Xian; Mehta, Jodhbir; Chan, Anita Sook Yee; Ong, Hon Shing (Frontiers in Medicine, 2022)
Purpose To describe a case series of peripheral ulcerative keratitis (PUK) as a paraneoplastic condition in three patients with known underlying systemic solid tumor malignancies. Observations Three patients with different systemic malignancies (1 recurrent breast cancer, 1 metastatic thyroid cancer, and 1 metastatic gastric adenocarcinoma) were identified to have PUK with significant corneal stromal melt. Autoimmune and infective work up for other etiologies were all negative. They all responded well to topical steroids and intravenous methylprednisolone. One patient had recurrences of her PUK and required repeated amniotic grafts and tectonic keratoplasties before her corneal condition stabilized. Conclusions and Importance PUK can be a rare manifestation of systemic solid tumour malignancies. Although PUK may not be an indicator of progression of the underlying malignancy, it can be sight-threatening. This case series highlights the necessity for clinicians to refer patients with systemic malignancies presenting with inflamed eyes for an early ophthalmological review. This facilitates the detection of this blinding disease, allowing for early therapeutic interventions and potentially better visual outcomes for these patients.